Selective imaging of quorum sensing receptors in bacteria using fluorescent Au nanocluster probes surface functionalized with signal molecules - Mukherji, Ruchira; Samanta, Anupam; Illathvalappil, Rajith; Chowdhury, Somak; Prabhune, Asmita; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2013)
Fluorescent ultrasmall gold clusters decorated with bacterial quorum sensing signal molecules, acyl homoserine lactone, are synthesized. These fluorescent probes are found to have emission in the near-infrared spectral region advantageous for bioimaging. Imaging studies using different. strains of bacteria with and without acyl homoserine lactone receptors with the aid of confocal microscopy have shown that the probe interacts preferentially with cells possessing these receptors. This indicates that, with appropriate surface functionalization, the Au clusters can be used for receptor specific detection with enhanced selectivity.
Keywords: Au nanoclusters; Biosensor; fluorescence imaging; quorum sensing

Microbial selenium nanoparticles (SeNPs) and their application as a sensitive hydrogen peroxide biosensor - Prasad, Kumar Suranjit; Vaghasiya, Jayraj V.; Soni, Saurabh S.; Patel, Jitesh; Patel, Rinkesh; Kumari, Madhu; Jasmani, Falguni; Selvaraj, Kaliaperumal (Applied Biochemistry and Biotechnology, 2015)
The cell-free extract, a crude enzyme (cytosolic and membrane fraction) obtained from an environmental isolate, Bacillus pumilus sp. BAB-3706 worked as excellent in reducing as well as stabilizing agent and facilitated the formation of stable colloidal selenium nanoparticles (SeNPs). Resulting nanoparticles were characterized using UV-vis spectrophotometer, TEM, EDAX, FT-IR and XRD, respectively. A working electrode was modified by coating the surface of indium tin oxide (ITO) with colloidal SeNPs. Successive additions of H2O2 (100 to 600 mu M) in conventional three electrodes system, cyclic voltammeter with potential scan rate 25.0 mV/s, in 0.1 M phosphate buffer solution (PBS) yielded increase in current. A perpetual amperometric response at fixed potential (-1.0 V) and at selected time interval of 100 s showed different magnitude of current at every addition of H2O2. The linear range of detection of H2O2 was from 5 to 600 mM (R (2) = 0.9965), while the calculated limit of detection was found to be 3.00 mu M. The current study suggested that microbial SeNPs can be used for fabrication of low cost, sensitive H2O2 biosensor.
Keywords: Biosensor; EDAX; Hydrogen peroxide; Selenium nanoparticles; TEM; UV-vis spectroscopy